Slow and diverse: Upslope expansion of tree species since 1854 in the Bavarian Alps (Germany) detected by citizen science - Sabine Rösler; Michelangelo Olleck; Karl H. Mellert; Jörg Ewald (Arctic, Antarctic, and Alpine Research)
We motivated mountain hikers to survey high-altitude occurrences of selected tree and shrub species in the Bavarian Alps in a citizen science portal and compared the observations with historical data collected by the botanist Otto Sendtner at the end of the Little Ice Age. For nine of ten species with sufficient numbers of historical and citizen science observations, currently uppermost outpost occurrences were verified after data curation and subsampling. Tree species of montane (Sorbus aucuparia: 342 m, Abies alba: 324 m, Acer pseudoplatanus: 273 m, Fagus sylvatica: 141 m) and of lower subalpine distribution (Betula pubescens: 278 m, Picea abies: 55 m) climbed significantly, whereas species found at the high subalpine tree line ecotone ascended less (Pinus mugo: 21 m, Larix decidua: 13 m, Alnus alnobetula: 6 m) or even appeared to lose elevation (Pinus cembra: −57 m). We explain the gap between realized and potential upslope shift of ca. 500 m suggested by the thermal elevation gradient by the lack of mature soils at high altitudes and low summit heights in the Bavarian Alps.